Urgensi Asbab An-Nuzul sebagai Langkah Awal untuk Menafsirkan Al-Qur’an - Adrian Adrian; Novi Andriani; Umi Nurhayati (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Understanding the Qur'an is not enough just to read the text raw or in the language we call it textual. Because it is very possible that there is a misinterpretation in understanding the true content of the Qur'an. So it is very important to have research on Asbab an-nuzul with a description approach to the analysis of the Qur'an, namely by looking from the side